Characterization of Osmotic Restraints on Lettuce Fruit Germination - REYNOLDS, T. (Oxford University Press, 1975)
Germination responses of fruits of lettuce ( Lactuca sativa L. cv. Arctic King) to solutions of mannitol or potassium chloride of different osmotic potentials were examined over a range of temperatures in both light and dark. The upper temperature limit (‘cut-off’) for germination was progressively lowered by solutions of increasingly negative osmotic potential. This observation explained inhibition of germination by solutions of low osmotic potential at single experimental temperatures, found in previous investigations. Solutions of the two compounds having equal calculated osmotic potentials produced an equal inhibitory effect. No evidence for solute absorption was seen. Solutions of lower osmotic potential were needed to produce the same inhibition of germination in light against total darkness and also at lower temperatures.